DNA hypermethylation of Kiss1r promoter and reduction of hepatic Kiss1r in female rats with type 2 diabetes. Issue 13 (9th December 2022) - Ziarniak, Kamil; Yang, Tony; Boycott, Cayla; Beetch, Megan; Sassek, Maciej; Grzeda, Emilia; Ma, Yuexi; Sliwowska, Joanna H.; Stefanska, Barbara
ABSTRACT: Kisspeptin, produced from the brain and peripheral tissues, may constitute an important link in metabolic regulation in response to external cues, such as diet. The kisspeptin system is well described in the brain. However, its function and regulation in the peripheral tissues, especially in relation to metabolic disease and sex differences, remain to be elucidated. As Kiss1 and Kiss1r, encoding for kisspeptin and kisspeptin receptors, respectively, are altered by overnutrition/fasting and regulated by DNA methylation during puberty and cancer, epigenetic mechanisms in metabolic disorders are highly probable. In the present study, we experimentally induced type 2 diabetes mellitus (DM2) in female Wistar rats using high-fat diet/streptozocin. We analysed expression and DNA methylation of Kiss1 and Kiss1r in the peripheral tissues, using quantitative-reverse-transcription PCR (qRT-PCR) and pyrosequencing. We discovered differential expression of Kiss1 and Kiss1r in peripheral organs in DM2 females, as compared with healthy controls, and the profile differed from patterns reported earlier in males. DM2 in females was linked to the increased Kiss1 mRNA in the liver and increased Kiss1r mRNA in the liver and adipose tissue. However, Kiss1r promoter was hypermethylated in the liver, suggesting gene silencing. Indeed, the increase in DNA methylation of Kiss1r promoter was accompanied by a reduction in Kiss1r protein, implying epigenetic or translational gene repression. Our results deliver novel evidence for tissue-specific differences in Kiss1 and Kiss1r expression in peripheral organs in DM2 females and suggest DNA methylation as a player in regulation of the hepatic kisspeptin system in DM2.